135k views
5 votes
Gianna is substituting t = 2 and t = 7 to determine if the two expressions are equivalent. 5 (2 t + 3) 5 t + 25 Which statement is true? Both expressions are equivalent to 35 when t = 2. Both expressions are equivalent to 85 when t = 7. Both expressions are equivalent to 60 when t = 7. The expressions are equivalent.

User Ranusharao
by
5.3k points

2 Answers

5 votes

Answer:

Both expressions are equivalent to 35 when t = 2.

User Damini Mehra
by
6.2k points
1 vote

Answer:

Both expressions are equivalent to 35 when t = 2

Explanation:

Given

Expression 1: 5(2 t + 3)

Expression 2: 5t + 25

When t = 2

5 (2 t + 3)

= 5(2*2 + 3)

= 5(4 + 3)

= 5(7)

= 35

5t + 25

= 5*2 + 25

= 10 + 25

= 35

When t = 7

5(2 t + 3)

= 5(2*7 + 3)

= 5(14 + 3)

= 5(17)

= 85

5t + 25

= 5*7 + 25

= 35 + 25

= 60

Both expressions are equivalent to 35 when t = 2

User Vadim Dissa
by
4.7k points